Istorijos didaktika ir istorijos sąmonė: tarpusavio santykio problema - Poviliūnas, Arūnas (Lietuvos istorijos studijos, 1997)
The paper discusses the general principles of compatibility between history and social science studies. Modernity has transformed the ancient belief that historia est magistra vitae (Cicero) and one common discourse of history has split into two different parts: academic history and didactics of history. This division has fostered the development of scientific history but, on the other hand, the gap between academic history and historical teaching has increased.Gradually, didactics of history have lost their raison d'être. How could didactics of history transfer the knowledge that was articulated in the discourse of professional and academic ("esoteric") history?The contemporary renaissance of didactics of history was caused by the newly articulated multidimensional subject, historical consciousness. The analysis of the structure of historical consciousness and the investigation of the factors of its development, etc., are building the bridges between the parts of the divided discourse of history and enabling history to regain its lost function.